(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In this paper we present about critically examines the reality of socioeconomic uplifting children belonging to Scheduled Caste and Scheduled Tribecommunities who have been in history barred from recognized tutoring the formerdue to their domination under caste feudal civilization and the latter due totheir spatial segregation and educational dissimilarity and ensuingmarginalization by overriding society.